Roadmap for creating a bilingual Uzbek-German electronic dictionary of forestry terms - Tilovova, Gavhar (Journal of Interdisciplinary Studies in Education, 2024)
This article deals with an important problem facing Uzbek lexicography, that is, the translation of forestry terms and lexicons into a bilingual Uzbek-German electronic dictionary. Naturally, the opinions of scientists regarding electronic dictionaries are presented, and the disparities between printed and electronic dictionaries are clarified. In addition, forestry terms are collected, summarized, and organized in a system, thus showing how electronic dictionaries can serve users better than their printed counterparts. Also, the article provides an overview of the four-step process of creating a dictionary designed to meet the demand for electronic dictionaries for forestry professionals. It explores the issues of developing bilingual electronic dictionaries. it is recommended that dictionaries be completely electronic in the future.